2022
DOI: 10.1080/2162402x.2022.2085432
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-associated macrophages in the tumor-adipose microenvironment facilitate breast cancer progression

Abstract: The tumor-adipose microenvironment (TAME) is a universal microecosystem, that is characterized by the dysfunction of lipid metabolism, such as excessive free fatty acids (FFAs). Macrophages are the most abundant immune cell type within TAME, although their diversity in the TAME is not clear. We first reveal that infiltration of M2-like macrophages in the TAME is associated with poor survival in breast cancer. To explore lipid-associated alterations in the TAME, we also detected the levels of FFAs transporters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 65 publications
4
54
0
Order By: Relevance
“…Notably, CFD functioned as an enhancer of tumor proliferation and cancer stem cell properties in breast cancers [ 49 ]. In another study, SPP1-associated macrophages in the tumor-adipose microenvironment facilitate breast cancer progression [ 50 ]. Interestingly, S100A8/A9, which are calcium-binding proteins that are secreted primarily by granulocytes and monocytes, may be associated with the loss of estrogen receptor and may be involved in the poor prognosis of Her2 + /basal-like subtypes of breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, CFD functioned as an enhancer of tumor proliferation and cancer stem cell properties in breast cancers [ 49 ]. In another study, SPP1-associated macrophages in the tumor-adipose microenvironment facilitate breast cancer progression [ 50 ]. Interestingly, S100A8/A9, which are calcium-binding proteins that are secreted primarily by granulocytes and monocytes, may be associated with the loss of estrogen receptor and may be involved in the poor prognosis of Her2 + /basal-like subtypes of breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…However, the relationship is greatly complex between tumors and immune cells. Previous studies have reported that M2 macrophage promote tumor invasion, progression and immune escape through increasing the expression of MHC class I molecules and secreting anti-inflammatory cytokines ( 29 31 ). Moreover, Tregs also inhibit the immune response, which led to immunosuppressive functions and accelerated the malignant tumors progression ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the human immune system is localized in a tissue-specific manner in diverse sites ( Weisberg et al, 2021 ). Functionally, tissue-specific immunity is observed to play a part in tumor development through various regulatory mechanisms ( Lei et al, 2020 ; Liu et al, 2022a ).…”
Section: Introductionmentioning
confidence: 99%